Copper (II) sulfate charring for high sensitivity on-plate fluorescent detection of lipids and sterols: quantitative analyses of the composition of functional secretory vesicles - Churchward, Matthew A. (Springer-Verlag, 2008)
A wide range of methods exist for the on-plate detection of lipids resolved by thin layer chromatography. Fluorescence generally offers improvements in sensitivity over methods that use colorimetric or simple densitometric detection. In this paper, we report that a classic cupric sulfate charring protocol produces a fluorescent signal that sensitively and quantitatively detects a wide range of phospholipids, neutral lipids, and sterols after automated, multi-development high performance thin layer chromatography. The measured lower limits of detection and quantification, respectively, were, on average, 80 and 210 pmol for phospholipids and 43 fmol and 8.7 pmol for sterols. The simple, inexpensive, and highly sensitive approach described here was used to quantitatively analyze the lipid and sterol composition of sea urchin cortical vesicles, a stage-specific model system used to study the mechanism of regulated membrane fusion.